Migraine Symptoms Improvement During the COVID-19 Lockdown in a Cohort of Children and Adolescents - Dallavalle, Gianfranco; Pezzotti, Elena; Provenzi, Livio; Toni, Federico; Carpani, Adriana; Borgatti, Renato (Frontiers in Neurology, 2020)
Background. Pediatric migraine is among the most common primary or comorbid neurologic disorders in children. Psychological stressors are widely acknowledged as potential triggers involved in recurring episodes of pediatric migraine. The present study was aimed to understand the effect of COVID-19 emergency on symptoms intensity and frequency in pediatric patients. Methods. 142 child and adolescent patients with a diagnosis of migraine were enrolled at the IRCCS Mondino Foundation in Pavia (Itally). Socio-demographic and clinical characteristics were obtained from medical records. An on-line survey was used to collect information on COVID-19 exposure, stress response to the lockdown period, anxious symptoms during COVID-19 emergency, as well as migraine symptoms intensity and frequency before and during the lockdown. Results. The great majority were outpatients (n = 125, 88.0%), 52 (36.6%) had migraine with aura, whereas 90 (63.4%) had migraine without aura. All the patients reporting worsening symptoms progression before COVID-19, had reduced intensity during the lockdown (χ2 = 31.05, p < .0001). Symptoms frequency reduction was observed in 50% of patients presenting worsening symptoms before the lockdown, 45% of those who were stable, and 12% of those who were already improving. All patients who had resolved symptoms before COVID-19 were stable during the lockdown (χ2 = 38.66, p < .0001). Anxious symptomatology was significantly associated with greater migraine symptoms frequency (χ2 = 19.69, p < .001). Discussion. A significant reduction of migraine symptoms intensity and frequency was observed in pediatric patients during the COVID-19 lockdown phase in northern Italy.